Cellulose recovery from sawdust : optimization of concentration, pretreatment time and temperature by using response surface methodology - Nasuha, Jalil (2010)
Cellulose is the most abundant organic material on earth that easily found nowadays in large amount which make it as a promising raw materials for the bio-energy production. The raw material that been used in this experiment is cellulose from meranti sawdust. The objective of this experiment is to obtain the maximum cellulose recovery from the sawdust by using the pretreatment methods and optimization using response surface methodology (RSM). The pretreatment process involved in this experiment were dilute sodium hydroxide NaOH, followed by peracetic acid pretreatment, PAA and dilute acid sulphuric H2SO4 pretreatment, followed by extraction and analysis using UV- Vis Spectrophotometer at the wavelength 320 nm. The conditions before the optimization are at temperature 150oC, 2.0% (v/v) diluted H2SO4 and 120 minutes of pretreatment time. After the optimization, the highest cellulose concentration (4.15922 mg/ml) can be achieved at 75oC, 82.96 minutes pretreatment time and at concentration 2.0% (v/v) diluted H2SO4.